Environment and Women Entrepreneurs in Albania - Zmijanej, Azra (European Journal of Economics and Business Studies, 2015)
Albania has become a much attractive environment for the development of women's entrepreneurship. If women are provided with the necessary resources, skills and opportunities to create strong businesses, and if they are willing to pursue the growth potential of these companies due to a more favorable environment, will benefit from economic growth. Promoting women entrepreneurs will create employment, empowerment and gender equality. But in fact the woman in the enterprise faces many challenges caused by various factors. In this study sought to analyze women entrepreneurs and their work environment in Albania and the challenges they face. It will identify policies for the development of enterprises managed by women in Albania. The data for this study were provided by various sources of literature. Secondary data are the result of the review of a wide and contemporary literature about women entrepreneurs, the environment and challenges. Primary data collection were carried out a series of in-depth personal interviews with some powerful women entrepreneurs in Albania. The results of this study show that woman has won respect in society and plays an important role in governance, political and private sector. It is clearly evidenced that women are becoming increasingly involved in social and economic life of the country and that an enabling environment for women's entrepreneurship, consolidates and supports their role.
Keywords: enterprising woman, empowering, environment, economic growth.